2018
DOI: 10.1007/978-3-030-01437-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Early Risk Detection of Anorexia on Social Media

Abstract: This paper proposes an approach for the early detection of anorexia nervosa (AN) on social media. We present a machine learning approach that processes the texts written by social media users. This method relies on a set of features based on domain-specific vocabulary, topics, psychological processes, and linguistic information extracted from the users' writings. This approach penalizes the delay in detecting positive cases in order to classify the users in risk as early as possible. Identifying anorexia early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Automated methods have been designed to detect signs of AN, some of which address the development of early detection approaches [6,7], as it has been proven that the signs and symptoms of mental disorders, including AN, can be traced using social media [6,[8][9][10][11][12][13]. The findings of such research have revealed patterns that can be relevant for the development of tools to detect harmful content [6] and to assist clinicians and psychologists in screening [10][11][12] and treatment proceedings [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automated methods have been designed to detect signs of AN, some of which address the development of early detection approaches [6,7], as it has been proven that the signs and symptoms of mental disorders, including AN, can be traced using social media [6,[8][9][10][11][12][13]. The findings of such research have revealed patterns that can be relevant for the development of tools to detect harmful content [6] and to assist clinicians and psychologists in screening [10][11][12] and treatment proceedings [6].…”
Section: Introductionmentioning
confidence: 99%
“…Automated methods have been designed to detect signs of AN, some of which address the development of early detection approaches [6,7], as it has been proven that the signs and symptoms of mental disorders, including AN, can be traced using social media [6,[8][9][10][11][12][13]. The findings of such research have revealed patterns that can be relevant for the development of tools to detect harmful content [6] and to assist clinicians and psychologists in screening [10][11][12] and treatment proceedings [6]. Research findings on these topics can also contribute to the improvement of the structure and services provided by online social platforms [6], which are a means through which people with mental disorders can find support for their recovery, as well as they can be used as tools to promote harmful content, which is the case for suicide promoters and pro-eating disorder (pro-ED) communities [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…These are features that have been used to address similar tasks, such as depression detection and eating disorders screening [ 7 , 31 ]. These models represent terms or sequences of terms (n-grams) based on their frequencies on the documents analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Paul, Kalyani and Basu [34] determined that the ada boost classifier was the best model to predict anorexia and depression, particularly when combined with the bag of words model. Additionally, Ramirez-Cifuentes and colleagues [35] compared different machine learning models and found that a logistic regression model detected anorexia behavior with the highest confidence level.…”
Section: Previous Researchmentioning
confidence: 99%